Preparation and Characterization of Thiosemicarbazones Corrosion Inhibition Effect and the Antimicrobial and Anticancer Effect on their Metal Complexes - Kashar, Tahani I.; Abdel-Motaal, Marwa; Emran, Khadija; Sukar, Noha A. (European Scientific Journal, ESJ, 2017)
Benzofurane and naphthofuranethiosemicarbazone ligands 2a (L1 )and 2b(L2) and their Cu(II), Co(II), Ni(II), and Pd(II) complexes have been synthesized and characterized by elemental analyses, molar conductance, magnetic susceptibility measurements, IR, NMR, and electronic spectral studies. IR spectra show that the ligands is coordinated to the metal ions in a didentate manner with N,S doner sites. In the presence of tow thiosemicarbazones ligands 2a(L1) and 2b(L2), the corrosion resistance of cast iron in 10.M H2SO4 increases in the order, 2b(L2) >2a(L1). The effect of studied ligands inhibits the corrosion of cast iron extent depending on the structure and high donation of π-electron present inhibitor. Co(II) and Pd (II) complexes possess higher antimicrobial activity than free ligands and other complexes. The [L1Pd Cl2]H2O complexe shows higher IC50 value of 4.6 µg/ml toward human breast cancer cell lines (MCF-7). For other complexes, they are in the range of 2.7– 4.3 µg/ml toward the former cells which is related to their metal complexing ability in enzymes.